The university in the 21st century : teaching the new Enlightenment at the dawn of the digital age - Elkana, Yehuda, 1934-2012; Klöpper, Hannes (Central European University Press, 2016)
This volume addresses the broad spectrum of challenges confronting the university of the 21st century. Elkana and Klöpper place special emphasis on the questions regarding the very idea and purposes of universities, especially as viewed through curriculum-what is taught-and pedagogy-how it is taught. The ideas recommended here for reform concern especially undergraduate or Bachelor degree programs in all areas of study, from the humanities and social sciences to the natural sciences, the technical fields, law, medicine, and other professions. The core thesis of this book rests on the emergence.